Revisiting Objectivity and its Application in the Modern Era - Kornelius Widyawan Haryanto (CV. Publikasi Indonesia, 2026)
This paper revisits objectivism and its relevance in the present. Objectivism is an understanding that believes in the process of thinking objectively and epistemically, and seeks to find factual truth, which is the truth that is found if a scientist or researcher does not inject interpretation into the object being interpreted. Modern science is very strongly attached to the notion of objectivism. This can be seen from how modern science, with all its methodological and empirical advantages, is able to answer many of the world’s problems. Thus, modern science has earned an honorable position in this world. However, the power of modern science in all its methodological and empirical forms has been criticized by three thinkers, namely Thomas Kuhn, Paul K. Feyerabend, and Richard Rorty. These three critics challenge the methodology and emphasize that nothing is purely objective. Thomas Kuhn emphasizes the existence of paradigms that influence researchers; Feyerabend stresses the need to open up space for creativity; Richard Rorty highlights the role of language and argues that something can be called truth if it is useful and situated in a particular temporal context. What these critics note has been addressed by the development of modern science today, through the recognition of paradigms and the openness of scientific methods to support innovation. Today, the word “objective” is used in the process of critical thinking. Critical thinking uses an objective process to select, test, and criticize information based on criteria regarding whether the information is valid and true, or merely a hoax. Therefore, the process of objective thinking today is still relevant to be used in the context of critical thinking.